2012
DOI: 10.1016/j.jtcvs.2012.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Aortopulmonary collateral flow volume affects early postoperative outcome after Fontan completion: A multimodality study

Abstract: Patients after bidirectional cavopulmonary connection routinely acquire a large amount of aortopulmonary collateral flow. The hemodynamic consequences of aortopulmonary collateral flow translate into adverse outcomes early after total cavopulmonary connection completion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 17 publications
1
52
0
1
Order By: Relevance
“…First, shunt flow may be significant, even in relatively small shunts, and also out of proportion to pressure gradients across chambers connected by the shunt [26,27]. Second, intra-and extra-cardiac shunts are not always apparent on echocardiography [2,3,28,29] and may need confirmation and quantification via alternative investigational modalities such as MRI or cardiac catheterization, which carry different risk profiles for the patient. Thus, UD may be a useful screening tool to evaluate patients who may need more detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, shunt flow may be significant, even in relatively small shunts, and also out of proportion to pressure gradients across chambers connected by the shunt [26,27]. Second, intra-and extra-cardiac shunts are not always apparent on echocardiography [2,3,28,29] and may need confirmation and quantification via alternative investigational modalities such as MRI or cardiac catheterization, which carry different risk profiles for the patient. Thus, UD may be a useful screening tool to evaluate patients who may need more detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not investigate the false positive cases (shunt detected by UD only) for the presence of extra cardiac shunts, which are common with some cardiac lesions [28,29]. Overall, the net effect may be to inflate the apparent false positive rate.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary vascular resistance (PVR) was calculated using the invasive pressure data and the CMR flows as the quotient between transpulmonary gradient and effective antegrade pulmonary flow defined as the sum of antegrade flow as measured in SVC and IVC plus collateral blood flow [8,10]. The transpulmonary gradient was calculated as the difference between mean pulmonary artery pressure and pulmonary capillary wedge pressure.…”
Section: Cardiovascular Magnetic Resonance Imaging (Cmr)mentioning
confidence: 99%
“…Highlighting the clinical significance of APC flow, three studies recently demonstrated that increased collateral flow before the Fontan operation was associated with longer duration of pleural drainage and prolonged recovery in the postoperative period [6][7][8]. However, the mentioned studies primarily focused on technical aspects of quantifying APC flow [2][3][4] or were assessed in patients after the Glenn-procedure [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…That provided a direct pathway for modest decompression of the venous side by the VAD as well as full offloading of the ventricle and full systemic support. The rational behind implantation of an oversized pump in our patient is based on the Fontan patient high-output state caused by aortopulmonary collaterals that can constitute a substantial fraction of the cardiac output, ranging from 11% to 62% [7]. Hence, VAD support with a normal index in these patients would deliver inadequate cardiac output owing to the substantial pulmonary collateral blood flow.…”
Section: Commentmentioning
confidence: 99%